2015
DOI: 10.4278/ajhp.130916-quan-479
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Sugar Content of Sports Drinks is Not Associated with Sports Drink Consumption

Abstract: There were disparities in sports drink consumption by sociodemographic characteristics and physical activity level; however, knowledge of sports drinks' sugar content was not associated with consumption. Understanding why some population groups are higher consumers may assist in the development of education, providing those groups with a better understanding of sports drinks' nutritional value and health consequences of excessive sugar consumption in any form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
5
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 23 publications
3
25
5
1
Order By: Relevance
“…Six cross-sectional studies (Fadupin, Ogunkunle, & Gabriel, 2014;Gase, Robles, Barragan, & Kuo, 2014;Huffman & West, 2007;Lee & Joo, 2016;Park, Onufrak, Sherry, & Blanck, 2014;Zytnick, 2015) and one case-study (Nelson & Hekmat, 1991) investigated the association between knowledge about sugar and sugar intake. Three of these cross-sectional studies (Gase et al, 2014;Lee & Joo, 2016;Park et al, 2014) reported an association between increasing knowledge about sugar and reduced consumption of food and beverages with sugar.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Six cross-sectional studies (Fadupin, Ogunkunle, & Gabriel, 2014;Gase, Robles, Barragan, & Kuo, 2014;Huffman & West, 2007;Lee & Joo, 2016;Park, Onufrak, Sherry, & Blanck, 2014;Zytnick, 2015) and one case-study (Nelson & Hekmat, 1991) investigated the association between knowledge about sugar and sugar intake. Three of these cross-sectional studies (Gase et al, 2014;Lee & Joo, 2016;Park et al, 2014) reported an association between increasing knowledge about sugar and reduced consumption of food and beverages with sugar.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…They may be equally unaware 2-3 servings a day of these drinks are equal to 4-6times the maximum recommended sugar intake for adolescents and others. 25 As well, even if they aware of the dangers of excess sugar and their presence in energy drinks, they may continue to ingest energy drinks or sports drinks regardless of sugar content, 27 with 11.5% of adults, especially 18-24-year-olds consuming sports and energy drinks three or more times per week. In addition, the many young people who continue to ingest regular soda, sweetened drinks and fruit drinks, may be more likely to also choose to drink sports and energy drinks on a weekly basis than those who don't, as well as suffering possible sleep loss, an obesity determinant.…”
Section: Resultsmentioning
confidence: 99%
“…e) Trying to understand why youth consumption of energy and sports drinks is widespread. 21,27 f) Encouraging school and college age students to do well in exams by studying hard and completing assignments by being physically fit, by getting enough sleep and by following sensible nutritional practices.…”
Section: Possible Solutionsmentioning
confidence: 99%
“…Current recommendations for refueling after exercise can be misleading, in particular for recreational athletes who are targeted by commercial marketing (Heneghan et al 2012;Zytnick et al 2015). In the current study, males and females resynthesized muscle glycogen at similar rates following glycogen depletion and consumption of two different diets (potato-based food items and common sport supplement products), leading to minimal differences during subsequent exercise performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, fitness in our study was lower for both sexes, underscoring the application of recovery recommendations across varied training statuses. A broadened application may be particularly important when considering recovery products that are often marketed to recreational athletes (Heneghan et al 2012;Zytnick et al 2015).…”
Section: Discussionmentioning
confidence: 99%